FOOD SECURITY, INCOME GROWTH AND GOVERNMENT EFFECTIVENESS IN WEST AFRICAN COUNTRIES - Olofin, Olabode Philip; Olufolahan, Toyin Joseph; Jooda, Taiwo Dayo (European Scientific Journal, ESJ, 2015)
While direct policies can ensure food security, this study poses that indirect policies can hinder or spur the expected success. Thus, the study examines the roles of government effectiveness and income growth on food security in West African Countries. Specifically, the study employed fixed effect Pooled Ordinary Least Square (OLS) method using annual secondary data between 1990 and 2014. Data on food security, income growth and government effectiveness were obtained from the ERS International Macroeconomic Data Set, World Bank Databank and World Governance Indicators respectively. The study finds positive relationship among food security; government effectiveness; and income growth. This relationship was only statistically significant for income growth and food security. This result suggests that, the influence of government effectiveness and income growth in ensuring food security in West Africa is pertinent in promoting food security. The study recommends that policies and programs that ensure quality civil service, policy formulation, implementation and credibility of governments’ commitment to such policies are fundamental for long-term food sustainability in West Africa.